Carrot solution culture bioproduction of uniformly labeled 13C-lutein and in vivo dosing in non-human primates. Issue 3 (February 2017) - Smith, Joshua W; Rogers, Randy B; Jeon, Sookyoung; Rubakhin, Stanislav S; Wang, Lin; Sweedler, Jonathan V; Neuringer, Martha; Kuchan, Matthew J; Erdman, John W
Lutein is a xanthophyll abundant in nature and most commonly present in the human diet through consumption of leafy green vegetables. With zeaxanthin and meso -zeaxanthin, lutein is a component of the macular pigment of the retina, where it protects against photooxidation and age-related macular degeneration. Recent studies have suggested that lutein may positively impact cognition throughout the lifespan, but outside of the retina, the deposition, metabolism, and function(s) of lutein are poorly understood. Using a novel botanical cell culture system ( Daucus carota ), the present study aimed to produce a stable isotope lutein tracer for use in future investigations of dietary lutein distribution and metabolism. Carrot cultivars were initiated into liquid solution culture, lutein production conditions optimized, and uniformly labeled 13 C-glucose was provided as the sole media carbon source for four serial growth cycles. Lutein yield was 2.58 ± 0.24 µg/g, and mass spectrometry confirmed high enrichment of 13 C: 64.9% of lutein was uniformly labeled and 100% of lutein was labeled on at least 37 of 40 possible carbons. Purification of carrot extracts yielded a lutein dose of 1.92 mg with 96.0 ± 0.60% purity. 13 C-lutein signals were detectable in hepatic extracts of an adult rhesus macaque monkey ( Macaca mulatta ) dosed with 13 C-lutein, but not in hepatic samples collected from control animals. This novel botanical biofactory approach can be used to produce sufficient quantities of highly enriched and pure 13 C-lutein doses for use in tracer studies investigating lutein distribution, metabolism, and function.